Amblyomma sparsum Neumann 1899 on migratory birds from Africa: First records in Italy - Michela Menegon; Elisa Mancuso; Marco Di Luca; Francesca Casale; Luis Neves; Andeliza Smit; Francesco Severini; Michele Castelli; Andrea Di Giulio; Silvio G. d'Alessio; Maria Goffredo; Federica Monaco; et al. (Ticks and Tick-Borne Diseases)
Migratory birds play an important role in transporting ixodid ticks and tick-borne pathogens between continents. During the Boreal spring, migratory birds reach Europe, mainly from sub-Saharan Africa or from northern African countries but not much is known about the diversity and ecology of the ticks they spread. From 2017 to 2022, in the framework of two consecutive projects focused on sampling migratory birds from Africa to Europe, a total of 27 immature Amblyomma ticks were collected from migratory birds, belonging to 8 species, captured on the Island of Ventotene, an important stop-over site in the Mediterranean Sea. In the absence of adult specimens, morphological identification was limited to assigning these ticks to the Amblyomma genus. In this study, sequencing and comparative analysis of three mitochondrial molecular markers (12S rDNA, 16S rDNA, COI) were performed to achieve taxonomic identification. Sequences obtained from Ventotene specimens matched at 100% identity with Amblyomma sparsum. In conclusion, this study documented that immature stages of this species belonging to the Amblyomma marmoreum complex reached the Pontine Islands for six consecutive years. The entry of alien tick species and their potentially transmitted pathogens deserves further study, also in light of the globally ongoing climate change.